Статистические процедуры при двухстороннем ограничении контролируемого параметра в процессе производства кабельно-проводниковой продукции - Голик, О.В. (Електротехніка і електромеханіка, 2016)
Рассмотрены вопросы статистического контроля в процессе производства массовой кабельно-проводниковой продукции на примере эмальпроводов. Получены результаты непосредственного контроля диаметра эмальпровода с полиимидной двухслойной изоляцией в непрерывном технологическом цикле. Представлена контрольная карта максимальной вероятности выхода диаметра за пределы определенного диапазона Розглянуті питання статистичного контролю у процесі виробництва масової кабельно-провідникової продукції на
прикладі емальпроводів. Отримані результати безпосереднього контролю діаметра емальдроту з поліімдною ізоляцією у неперервному технологічному циклі. Представлена контрольна карта максимальної ймовірності виходу діаметру
за межі визначеного діапазону Purpose. To consider issues of statistical control in the process
of mass production of cable and wire products on the example of
enameled wire. To analyze the results of direct control of the
diameter of the wire in two-layer polyimide insulation in a
continuous technological cycle. To submit to the control map of
maximum probability of the exit diameter outside a specific
range. To analyze the conditions under which maximum
sensitivity of process control. Methodology. Study of the
sensitivity of the control map of maximum probability of the exit
option for regulatory of limit in the field deviations of the
centered parameter close to zero. The existence of stable trends
in the change of a controlled parameter can reduce the
sensitivity of punishment to instability of the process. Results. To
achieve maximum sensitivity of control of the technological
frontier should be selected on the basis of the achieved level of
the average value of the parameter and its statistical scattering.
Process boundaries must be changed in accordance with the
achieved level of the average value of the parameter and its
statistical scattering. Such a change may serve as a quantitative
indicator of trends in the increase or decrease in the reliability
of the technological system. Originality. In particular the tasks
of current control using engineering tolerances for controlled
parameter are impractical. Control on Pmax should be directed
to the exception of manufacturing, the parameters of which
extend beyond the technical tolerances. Practical value. The
exception is the manufacture of bulk cable products, the
parameters of which extend beyond the technical tolerances.